Admiral Kolchak in Omsk: on history of Civil War in Russia and geopolitical redistribution of Europe after First World War - S. V. Novikov (Омский научный вестник: Серия "Общество. История. Современность")
The article is devoted to the study of the circumstances of coming to power in the anti-Bolshevik Omsk of Admiral A. V. Kolchak. He concentrated in his hands the executive, legislative, judicial and military power becoming the Supreme Ruler of Russia and the Supreme Commander-in-Chief. The author comes to the conclusion that the appearance of A.V. Kolchak in Omsk was a consequence of the contradictions between British and French politicians, and the admiral himself, relying on the British, was a victim of a redivision of the world following the First World War